Morphological changes in the ovaries and other organs of the collared lemming ( Dicrostonyx groenlandicus ) during pregnancy and pseudopregnancy - Hasler, J. F.; Banks, E. M. (Canadian Journal of Zoology, 1975)
The histology of the ovary and changes in organ weights were studied during pregnancy and pseudopregnancy in collared lemmings (Dicrostonyx groenlandicus). Females paired with vasectomized males mated on the average every 10 days. Corpus luteum diameter reached a maximum on day 8 but decreased greatly by day 10 in pseudopregnant females. Corpus luteum diameter in pregnant females reached a maximum by day 14 and had decreased 2 days post partum. Ovaries, preputials, and adrenals increased in weight during pregnancy and pseudopregnancy. Implantation occurred during the 5th day post coitus. Corpora albicantia disappeared within 77 days after parturition but placental scars were visible for at least 172 days after parturition.